2022
DOI: 10.1161/circheartfailure.121.008550
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Protects Against Heart Failure Via Expansion of Myeloid-Derived Suppressor Cells Through Regulating IL-10/STAT3/S100A9 Pathway

Abstract: Background: Exercise training (ET) has a protective effect on the progression of heart failure, however, the specific mechanism has not been fully explored. Myeloid-derived suppressor cells (MDSCs) are a group of myeloid-derived immunosuppressive cells, which showed a protective effect in the progression of heart failure. Thus, we hypothesized that the protective effect of ET on heart failure may be related to the infiltration of MDSCs. Methods: C57BL/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…In addition, treadmill exercise reduced chronic allergic lung inflammation and airway remodeling in mice ( Vieira et al, 2007 ). Treadmill exercise could increase myeloid-derived suppressor cells (MDSCs) by stimulating the secretion of IL-10 from macrophages through the IL-10/STAT3/S100A9 signaling pathway, thereby achieving heart protection ( Feng et al, 2021 ). Depression symptoms were alleviated by reducing the number of microglia and inhibiting microglial activation and neuroinflammation in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, treadmill exercise reduced chronic allergic lung inflammation and airway remodeling in mice ( Vieira et al, 2007 ). Treadmill exercise could increase myeloid-derived suppressor cells (MDSCs) by stimulating the secretion of IL-10 from macrophages through the IL-10/STAT3/S100A9 signaling pathway, thereby achieving heart protection ( Feng et al, 2021 ). Depression symptoms were alleviated by reducing the number of microglia and inhibiting microglial activation and neuroinflammation in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for qPCR was described previously ( Feng et al, 2022 ). Briefly, the total RNA of rats’ heart samples was isolated using Trizol reagent (Takara Bio, Japan.).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, MDSCs have also been shown to play a cardioprotective role; Zhou et al reported that MDSCs could exert anti-inflammatory effects on cardiomyocytes through secretion of IL-10 and NO, thereby alleviating heart failure (122). Another study showed that exercise training stimulated macrophages to induce MDSCs proliferation through IL-10/STAT3/S100A9 signaling pathway, and the increase in MDSCs significantly improved heart failure symptoms (123).…”
Section: Myeloid-derived Suppressor Cellsmentioning
confidence: 99%